٢٠٠٣- العلاقات السودانیة – الاثیوبیة ١٩٥٤ (Journal of the College of Education for Women, 2019)
The Horn of Africa region is one of the most important strategic areasaccording to the geopolitical classification of the world, thus the region held agreat importance throughout two historical ears specially for possessinginternal attraction factors either for it’s natural resources or for what itrepresent as a central point for maritime transport. Adding to that the regionwitnessed ethnic and political contradictions as well as cultural differences.Because of the importance of the Horn of Africa region it has becomeFulcrum of the conflict among European powers Which worked hard toimpose its influence on this region for the purpose of monopolizing theGeographical and strategic advantages which managed European powers,after the Berlin Conference in (1884-1885) to impose it’s influence on someparts of the region Prompting Ethiopia to coordinate with the Western powersPretext that it is a Christian state to cooperate with them in the division of theterritory of the Horn of Africa, Ethiopia, managed to share their dreams incontrolling the States (Eritrea, Djibouti, Somalia, Sudan) and draw politicalboundaries. This division disregarded (The tribes living on both sides of theborders) the right to self-determination, imposing impact on Ethiopia'srelations with neighboring countries, including Sudan from the westThe division led both countries to fall into conflicts as well as bordersand ethnic problems which lasted for several political eras and for severalsuccessive regimes, it also gave way to regional powers allowing thesepowers to practice there role to put pressure on many Arab countries,especially Egypt and Sudan, which has had an impact on both countriessafety.The entitled thesis (Sudanese-Ethiopian contemporary relations) willdiscuss the nature of the relation that linked the two countries especially inlight of successive Sudanese regimes which significantly influenced thecourse of that relation.